Perancangan Motion Graphic Iklan Layanan Aplikasi Garuda Kasir Sebagai Media Promosi Di Sosial Media - Syarifah Shakila Alatas; Afdhol Wahyudi (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2020)
Guidance programme that doesn’t provide appropriate information to the student will prevent them from progress their ideas even further as they want the opportunity to learn and benefit on the information given. Giving the broad extent of information given to the student, they need to be clear and be able to differentiate which information is clear and which is not clear, and what type of information is related to services, facts that have not changed and which facts can change over time. The solution that will be used to solve the problem is by using motion graphic as an intermediate platform aimed at the audience/community in delivering application service information which will later be shared with social and public media to attract the attention of audiences with interesting animations from different aspects of motion graphic